Deliberation of private input dealers towards public extension services delivery system: An approach based on subjectivity analysis - Kuppachari, Pachaiyappan; Tiwari, Rupasi; Chander, Mahesh; Bardhan, Dwaipayan (Indian Journal of Dairy Science, 2020)
The present study was attempted to subjectively assess the amenability & readiness of private input dealers in deliverance of dairy and other livestock extension services. â€œQ Methodologyâ€ was the technique adopted and the method was carried out in the selected Kancheepuram and Villupuram districts of Tamil Nadu state involving 26 identified input dealers, handling dairy and other livestock input items. The attentiveness of the respondents towards their inclusion in the public extension services systemâ€™, were estimated subjectively with the help of attitude statements. Principle Component Analysis (PCA) method of statistical estimation was done and the categorized statements were clubbed into four identified discourses based on the obtained Eigen values. Q methodology â€“ subjectivity analysis classified on four defined discourses viz., â€œRisks and opportunities in the endeavorâ€, â€œSocio-economic empowerment in the undertakingâ€, â€œElements of collaboration in the endeavorâ€ and â€œPossible refraining behavior / escapism in the processâ€; in a nutshell had cued positive agreement of input dealers to the statements supporting to their inclusion in public extension service stream.